2015
DOI: 10.24252/lp.2015v18n1a5
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kemampuan Baca Tulis Al-Qur’an Terhadap Hasil Belajar Tafsir Mahasiswa Fakultas Tarbiyah Dan Keguruan Uin Alauddin Makassar

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh kemampuan baca tulis al-Qur'an terhadap hasil belajar tafsir mahasiswa semester II angkatan 2013/2014 Jurusan Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Alauddin Makassar. Metode penelitian yang digunakan ialah kuantitatif. Variabel dalam penelitian ini adalah Kemampuan baca tulis al-Qur'an (X), dan hasil belajar tafsir (Y). Populasi dalam penelitian ini adalah mahasiswa semester II angaktan 2013/2014. Jumlah responden sebanyak 40 Mahasiswa deng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Other studies have shown that the ability to read the Qur'an is significantly and positively correlated to the learning outcomes of Medan POLYTECHNIC students (Suherman, 2017). (Nuryamin, 2015) at UIN Alaudin Makasar shows that the ability to read and write the Qur'an influences the Tafsir subject. This ability can certainly also affect other similar subjects such as the science of hadith, usul fiqh, muamalah fiqh, Arabic and others.…”
Section: Waqaf Wa Ibtida 'mentioning
confidence: 99%
“…Other studies have shown that the ability to read the Qur'an is significantly and positively correlated to the learning outcomes of Medan POLYTECHNIC students (Suherman, 2017). (Nuryamin, 2015) at UIN Alaudin Makasar shows that the ability to read and write the Qur'an influences the Tafsir subject. This ability can certainly also affect other similar subjects such as the science of hadith, usul fiqh, muamalah fiqh, Arabic and others.…”
Section: Waqaf Wa Ibtida 'mentioning
confidence: 99%
“…Both of these sources require special skills, namely the ability to read the Qur'an properly and correctly. [4] at UIN Alaudin Makassar shows that the ability to read and write the Qur'an has an effect on the Tafsir course. Other research shows that the ability to read the Qur'an is significantly and positively correlated with the learning outcomes of Medan Polytechnic students [5].…”
Section: Introductionmentioning
confidence: 99%
“…(Nurul Hijrah dkk., 2022) menjelaskan lebih rinci bahwa membaca disini berarti membaca dan menulis, tetapi kegiatan membaca mencakup banyak aspek antara lain: berpikir, emosional, serta melaksanakan halhal yang baik dan bermanfaat sesuai dengan anjuran (Hernowo, 2003), Sedangkan kata tulis berarti batu, maksudnya batu disini adalah tempat untuk menulis. Kemudian kata tulis ditambah ahiran-an menjadi tulisan, artinya tulisan berarti hasil tulisan (Nuryamin, 2015).…”
unclassified